Income inequality in today’s China - Hasík, Gabriel (Asia in World Politics: Past, Present, and Future, 2021)
This chapter is focused on the problem of income inequalities in contemporary China which is one of the biggest developmental challenges for this country. First this part of the analysis includes general overview on studied problem putting emphasis on instrument for measuring income inequalities, and general drivers of this phenomenon. Second part is concentered on the nature of this problem in China since the late 1970s, when country has faced a period of rapid economic development. Chapter also points out attempts taken by the Chinese government to reduce income inequalities.